Flash-based algorithms of database buffer management - Kuznetsov, S.D.; Prokhorov, A.A. (Trudy Instituta sistemnogo programmirovaniâ, 2018)
One of the most important ways of increasing the speed of the modern databases is to cache frequently used data in RAM. Classical replacement policies are intended to minimize the number of buffer pool faults. This optimization method implicitly relies on the fact that the speeds of reading and writing to the hard disc are equal. Gradual technology improvement and cost reduction of flash memory have led to the creation of solid-state data storages (SSD) that are now increasingly used in personal computers and storage systems. Flash drives have advantages over traditional hard drives, high read and write speeds and significantly small time of random data access are the most important of them. However, the most popular flash-memory types read data at a higher speed than write it. Due to this feature the use of classical replacement algorithms of disk data caching is ineffective. This paper reviews recently developed algorithms of database buffer pool management designed to work with flash memory drives: CFDC (Clean First – Dirty Clustered), CASA (Cost-Aware Self-Adaptive), SAWC (Self Adaptive with Write Clustering), and FD-Buffer. Some of these algorithms demonstrate significant advantages over the classical algorithm LRU.